2018
DOI: 10.1088/1361-648x/aaf54c
|View full text |Cite
|
Sign up to set email alerts
|

Exciting vibrons in both frontier orbitals of a single hydrocarbon molecule on graphene

Abstract: Vibronic excitations in molecules are key to the fundamental understanding of the interaction between vibrational and electronic degrees of freedom. In order to probe the genuine vibronic properties of a molecule even after its adsorption on a surface appropriate buffer layers are of paramount importance. Here, vibrational progression in both molecular frontier orbitals is observed with submolecular resolution on a graphene-covered metal surface using scanning tunnelling spectroscopy. Accompanying calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 80 publications
2
15
0
Order By: Relevance
“…The experimental and theoretical findings presented in this work likewise shed light onto the notion of electronic decoupling, which is generally used to characterize the extent of hybridization of an adsorbate with the hosting substrate. The weak hybridization is often attributed to the submolecular resolution in STM images of adsorbed molecules, [ 206–210 ] the occurrence of electronic states, [ 211–219 ] vibrational quanta, [ 220–224 ] and fluorescence photons [ 225–237 ] with particularly sharp spectroscopic line shapes. In the case of graphene, the results summarized here are able to provide a more precise and quantitative description of the hybridization.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…The experimental and theoretical findings presented in this work likewise shed light onto the notion of electronic decoupling, which is generally used to characterize the extent of hybridization of an adsorbate with the hosting substrate. The weak hybridization is often attributed to the submolecular resolution in STM images of adsorbed molecules, [ 206–210 ] the occurrence of electronic states, [ 211–219 ] vibrational quanta, [ 220–224 ] and fluorescence photons [ 225–237 ] with particularly sharp spectroscopic line shapes. In the case of graphene, the results summarized here are able to provide a more precise and quantitative description of the hybridization.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…The satellite structure is reminiscent of vibronic sidebands, which occur due to the simultaneous excitation of a vibrational mode upon charging [22,25,[57][58][59][60][61]. The sidepeaks should thus obey the same symmetry as the parent orbital state [62][63][64]. In the simplest case, these excitations can be described within the Franck-Condon model (see sketch in Figure 6c).…”
Section: Vibronic Excitations Of Tcnq On Mos 2 On Ag(111)mentioning
confidence: 99%
“…The different symmetries of the displacement patterns may explain why the 1349 cm −1 (1594 cm −1 ) mode couples particularly well to the HOMO (LUMO). It has recently been shown that matching symmetries of vibrational and electronic states are favorable for the occurrence of vibronic progression [9]. Using Equation 3, the Huang-Rhys factor for vibronic progression of the HOMO (LUMO) is approx.…”
Section: Graphene-c 42 H 28mentioning
confidence: 99%
“…In contrast, vibrational spectroscopy at the single-molecule level is scarce. Scanning tunneling spectroscopy (STS) of vibronic levels of 1,3,5tris(2,2-dicyanovinyl)benzene on graphene-covered h-BN on SiO 2 [4], of cobalt phthalocyanine molecules on graphenecovered SiO 2 /Si samples [5] as well as on h-BN-covered Ir(111) [6], of conjugated oligohenylenes on h-BN-covered Cu(111) [7], of manganese phthalocyanine on h-BN-covered Rh(111) [8], and of 5,10,15,20-tetraphenylbisbenz [5,6]indendo [1,2,3-cd:1′,2′,3′-lm]perylene on graphenecovered Ir(111) [9] have been reported so far. In these studies molecular orbitals, the highest occupied molecular orbital (HOMO) or the lowest unoccupied molecular orbital (LUMO), appear with spectroscopic fine structure in differential conductance (dI/dV, I: tunneling current, V: bias voltage) data, which is assigned to vibronic progression induced by a single group of molecular vibrations with similar quantum energies.…”
Section: Introductionmentioning
confidence: 99%